In vitro direct organogenesis of the medicinal single-mountain local prioritized vulnerable Greek endemic Achillea occulta under different medium variants - Virginia SARROPOULOU; Eleni MALOUPA; Katerina GRIGORIADOU (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2023)
Achillea species are of high medicinal value based on their use in traditional medicine and their content in secondary metabolites with potential application in dermatology and cosmetic industry. Achillea occulta is a single-mountain local prioritized vulnerable Greek endemic encountering propagation problems through seeds and root division. In vitro propagation can be used for the rapid and mass production of clonal plants complying with phytochemical and sanitary quality criteria. In this study, several culture medium variants were tested including the effect of different indole-3-butyric acid (IBA) concentrations with 6-benzyladenine (BA), different cytokinin types, agar concentrations, and zeatin (ZT) sterilization methods on in vitro shoot proliferation, as well as the effect of different auxin types and concentrations on in vitro rooting and ex vitro survival rate of shoot-tip explants. The results showed BA was the most preferable cytokinin type as evidenced by all proliferation attributes and autoclaved ZT provided longer shoots. Therefore, the two more promising and cost-effective treatments for proliferation were 2.2 μM BA + 0.25 μM IBA or 4.4 μM BA + 0.5 μM IBA after 21 days of culture on modified Murashige-Skoog (MS) medium (x2 Fe) enriched with 20 g L-1 sucrose and 6-7 g L-1 Agar (90-93.8% shoot formation, 2.7-2.9 shoots 0.4-0.6 cm long, 2.5-2.6 proliferation rates). Explants rooted better after 21 days of culture on plain MS medium with 2 μM IBA or 1 μM α-naphthalene acetic acid (NAA) (13.3-20% rooting, 1-1.5 roots 1.8-2 cm long). NAA gave more roots, IBA longer roots, while both auxins exhibited highest rooting (13.33-20%) and ex vitro survival rates (50-66.7%).